2020
DOI: 10.1029/2020jd033132
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization Impact on Regional Wind Stilling: A Modeling Study in the Beijing‐Tianjin‐Hebei Region of China

Abstract: Prominent slowdown in near-surface wind speed (NSWS) has been observed in the Beijing-Tianjin-Hebei (BTH) region of China, which has important implications for regional haze mitigation and wind energy production. Other than large-scale climatic variation, this decline is suspected of being linked to the impact of urbanization. Based on nested high-resolution simulations using the Weather Research and Forecasting model, we assessed quantitatively the respective roles of urban development and anthropogenic heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…In this paper, the wind speed change mechanisms in China are analyzed from two aspects: upper wind elds and uneven warming between high and low latitude zones. In addition to the above two aspects, the variation of near-surface wind speed may be closely related to the aerosol forcing and land use changes (Deng et al 2021a), urbanization (Wang et al 2020), larger-scale ocean-atmosphere circulations (Zha et al 2021), Arctic Oscillation (AO) (Ge et al 2021), etc. In the future, it would be of great signi cance to study the variation mechanisms of near-surface wind speed in China from various aspects, and to quantitatively identify the main in uencing factors of near-surface wind speed variations in different periods and regions.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the wind speed change mechanisms in China are analyzed from two aspects: upper wind elds and uneven warming between high and low latitude zones. In addition to the above two aspects, the variation of near-surface wind speed may be closely related to the aerosol forcing and land use changes (Deng et al 2021a), urbanization (Wang et al 2020), larger-scale ocean-atmosphere circulations (Zha et al 2021), Arctic Oscillation (AO) (Ge et al 2021), etc. In the future, it would be of great signi cance to study the variation mechanisms of near-surface wind speed in China from various aspects, and to quantitatively identify the main in uencing factors of near-surface wind speed variations in different periods and regions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that in recent years, the global wind speed also has had a weak mean state and variability. Many previous studies have suggested that large‐scale circulations and urbanization are important factors to the observed wind stilling 40,68–70 . The Siberian high pressure impacts the NWS variation on the decadal timescale by influencing weather regime occurrence over Eastern Asia 68 .…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…The Siberian high pressure impacts the NWS variation on the decadal timescale by influencing weather regime occurrence over Eastern Asia 68 . As for urbanization, it ignored in the regional NWS decline, but it does not play a dominant role 40 . More research is required to make out the reasons for the long‐term trends in the mean state for NWS.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The most distinctive manifestation of anthropogenic LUCC is urbanization (Zha et al 2016;Wang et al 2020). Effects of urbanization on NWS were revealed by both observation and numerical simulation (Tab.…”
Section: Other Potential Drivers Of Nws Changesmentioning
confidence: 99%